Playing, earning, crashing, and grinding: Axie infinity and growth crises in the Web3 economy - Jordan Ali; Gili Vidan (Big Data & Society)
Axie Infinity is a blockchain-based video game offering players the chance to earn crypto tokens in exchange for their time spent playing the game. During the COVID-19 lockdowns, the game's popularity surged alongside the crypto market and stories of early adopters’ quick returns on investments circulated among online crypto and Web3 communities. As the game's rapidly growing userbase plateaued, the community experienced several growth-related crises, one of which saw the value of the game's tokens crash. But players were not passive victims of these developments. They responded by creating a “scholarship” program to secure the flow of new players to the platform and actively commented on their commitment to the “grind” of playing the game to recoup their investments. This article treats the trajectory of Axie Infinity as both an exemplar case study of broader dynamics in the crypto gaming landscape—a process we call the economization of play —and as a unique site in which players were not simply duped by the promise of the game, but were responding to crises proactively with risk mitigating and rationalizing strategies.